Morphology of Naturally-Occurring Tuberculosis in Cattle Caused by Mycobacterium caprae. (January 2020) - Ozturk-Gurgen, H.; Rieseberg, B.; Leipig-Rudolph, M.; Straubinger, R.K.; Hermanns, W.
Summary: This study describes the pathomorphological alterations of bovine tuberculosis through gross and histopathological examinations, assessment of the distribution of lesions and the demonstration of mycobacteria. Samples from lungs, liver, small intestine, their regional lymph nodes and retropharyngeal lymph nodes were collected from 84 cattle with tuberculosis from the Allgäu, Germany. Organs were evaluated grossly, histopathologically and by transmission electron microscopy. Mycobacteria and mycobacterial antigens were demonstrated using acid-fast staining and immunohistochemistry (IHC). Bacteriological tests revealed Mycobacterium caprae in all animals. Gross alterations were classified into five patterns (I to V) with an additional pattern of acute exudative pulmonary inflammation (pattern VI). Histological lesions were classified into four types (1–4) with additional lesions occurring in lungs only. Acid-fast staining revealed a low number of bacteria in all tissues, while IHC showed comparatively more mycobacterial antigens within the lesions and also at their periphery. The alimentary tract (68%) was the main portal of entry followed by an aerosol infection (19%). It was assumed that the observed lesions reflect a continuous primary period of infection; there were no lesions typical of a secondary (post-primary) period, as reported in man and also described in the older literature on bovine tuberculosis. The broad spectrum of changes described formerly was not observed in the present cases and the route of infection and nature of acid fast staining showed differences when compared with previous studies of naturally-occurring bovine tuberculosis.